2020
DOI: 10.3390/info11120542
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Prediction Model Using Extreme Learning Machine: The Case Study of Tangier, Morocco

Abstract: An efficient and credible approach to road traffic management and prediction is a crucial aspect in the Intelligent Transportation Systems (ITS). It can strongly influence the development of road structures and projects. It is also essential for route planning and traffic regulations. In this paper, we propose a hybrid model that combines extreme learning machine (ELM) and ensemble-based techniques to predict the future hourly traffic of a road section in Tangier, a city in the north of Morocco. The model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The results of the evolution of model performance as a function of hidden neuron numbers demonstrate that the ideal number of hidden neurons with accurate results for our training dataset is 250 neurons. This approach has been detailed in a recent study [7]. For the purpose of Bagging base estimators, the number of ELM estimators was set to 10 since it shows better accuracy and requires less computation time.…”
Section: Extreme Learning Machinementioning
confidence: 99%
“…The results of the evolution of model performance as a function of hidden neuron numbers demonstrate that the ideal number of hidden neurons with accurate results for our training dataset is 250 neurons. This approach has been detailed in a recent study [7]. For the purpose of Bagging base estimators, the number of ELM estimators was set to 10 since it shows better accuracy and requires less computation time.…”
Section: Extreme Learning Machinementioning
confidence: 99%
“…The confidence is 1 for a rule (𝐴 → 𝐵) if the consequent and antecedent always occur together. It is expressed by (2): The lift of the rule (A→B) is the confidence of the rule divided by the support of the consequent B. A higher lift value between two variables means a higher correlation between them.…”
Section: Association Rule Miningmentioning
confidence: 99%
“…When comparing the model findings to the actual results, it was shown that the model can meet the criteria for bus arrival prediction. Jiber et al [9] conducted a road traffic forecast study in Morocco using data from the Moroccan center for road studies and research. They merged Ensemble-based ELM approaches based on the number of neurons in the hidden layer.…”
Section: Related Workmentioning
confidence: 99%